Effect of exogenous lead on growth and carbon metabolism of pea (Pisum sativum L) seedlings - Devi, Rachana (Springer-Verlag, 2012)
The present study investigated the effect of exogenous lead (Pb) on seedling growth, carbohydrate composition and vital enzymes of sucrose metabolism, starch degradation, pentose phosphate pathway and glycolysis in pea seedlings. With 0.5 mM Pb, reduction of about 50 % in shoot and 80 % in root lengths was observed. At 5 and 7 days of seedling growth, cotyledons of Pb-stressed seedlings had about 25–50 % lower α- and β-amylase activities resulting in their higher starch content. Low starch content in the cotyledons of control seedlings at days 1, 3, 5 and 7 may be due to higher investment of carbon for seedling growth. Seedlings exposed to Pb showed significant inhibition of about 30–50 % in acid invertase activity in the growing tissues i.e. roots and shoots. Sucrose content increased by 10–20 % in shoots with much larger increase in cotyledons at 5–7 days of growth in Pb-stressed seedlings. In stressed seedlings, sucrose synthase (SS) and sucrose-6-phosphate synthase (SPS) enzymes were down regulated in the roots but SS activity was up regulated in the cotyledons leading to increased sucrose content. Exogenous Pb increased the activities of glucose-6-phosphate dehydrogenase (G6PDH) and 6-phosphogluconate dehydrogenase (6PGDH) in the cotyledons. Down regulation of G6PDH and up regulation of hexokinase (HXK) in the roots and shoots of stressed seedlings indicated that hexoses could be utilised preferably for glycolysis rather than pentose phosphate pathway in these tissues. Due to limited supply of sugars to growing tissues in the stressed seedlings, increased HXK may play a role in sugar sensing. Phosphoglucomutase (PGM) activity was maximum in the cotyledons and minimum in roots showing its importance in the conversion of glucose-1-phosphate into glucose-6-phosphate. Reduced seedling growth observed in the presence of exogenous Pb was mainly due to the decrease in the activities of amylases and invertases in the cotyledons and growing tissues respectively. Further biosynthetic capacity of the roots and shoots was down regulated in the pea seedlings due to reduced efficiency of pentose phosphate pathway under Pb toxicity.